Ujitoksisitasakut ekstrakbatangpisangambon(Musa paradisiacavar sapientum) terhadap hati mencit (Mus musculus) dengan parameter LD (Acute toxicity test of ambonese banana (Musa paradisiaca var sapientum) stem extract in liver of mice (Mus musculus) with LD 50 parameters 50 - Hendrik Setia Budi; Ira Arundina; Retno Indrawati; Leonita Widyana Mahardikasari (Journal of Dentomaxillofacial Science, 2014)
The sap of ambonese banana (Musa paradisiaca var sapientum) contain flavonoids, saponins, tannins which have beenwidely used by people in Trunyan Bali as traditional medicine on wound healing, and it has been reported as apotential wound healing after tooth extraction. The aim of this research was to determine the level of safety of usingherbal medicine, ambonese banana stem extract on histopatology liver of mice with LDparameters. This experimentalstudy was performed bythe post test only controlled group design. The sample were 28 mice (Mus musculus) randomlydivided into 4 groups. K group as control group was given aquadest. P1, P2, and P3, as treatment groups were givenambonese banana stem extract with dose 0.42g/20gbw, 2.1g/20gbw, 4.2g/20gbw. The extract was given per-oral withsonde on the first day. On day 3, the mice were terminated, and the livers were microscopically histopathological observed. The observed at 3th50 day, there were no deaths in every groups of mice (K, P1, P2, and P3) on the third day observation. Kruskal Wallis test showed there was not significant difference in histopathological appearance on liverof mice (p=0.771). It wasconcluded that the maximumsafety dose that can still be administered is 0.42g/20gbw followingthe LDparameter. Theacute toxicity test of ambonese banana stem extract did not show necrosis on liver but it showedthe highest simple degeneration than all groups which were given 0.42g/20gbw dose.